Estimation of genetic components for plant growth and physiological traits of wheat (Triticum aestivum L) under normal and stress conditions - Naeem, MK; Ahmed, M; Noreen, S; Shah, MKN; Iqbal, MS (SAARC Journal of Agriculture, 2015)
This study was conducted to investigate the genetic variability of plant growth and physiological characters in thirty wheat genotypes under normal and drought stress conditions. Selection of important plant growth and physiological traits are essential component for wheat yield improvement. For this purpose, an experiment was conducted in the glasshouse during 2012-13 to estimate the extent of genetic components viz., genetic variance, coefficient of variability and broad sense heritability for plant growth and physiological traits under normal and drought stress conditions. Higher genetic variance was observed between the genotypes for the cell membrane stability, excised leaf water loss, relative water content, proline, sugar and glycine betain under both conditions. This suggested that these indices can be used as direct selection criteria for wheat improvement. While excised leaf water loss and fresh root weight revealed the least variability for GCV and PCV correspond to high heritability under stress condition. Hence, these traits can be used as indirect selection criteria under stress condition. SAARC J. Agri., 13(1): 90-98 (2015)